Core–sheath nanofibrous membranes based on poly(acrylonitrile‐butadiene‐styrene), polyacrylonitrile, and zinc oxide nanoparticles for photoreduction of Cr(VI) ions in aqueous solutions. Issue 9 (30th August 2019) - Castro‐Ruíz, Andrés; Rodríguez‐Tobías, Heriberto; Abraham, Gustavo A.; Rivero, Guadalupe; Morales, Graciela
ABSTRACT: This investigation addresses the design of a series of poly(acrylonitrile‐butadiene‐styrene)/polyacrylonitrile–zinc oxide(ABS/PAN–ZnO) membranes by coaxial electrospinning. In the first instance, an optimization of ABS and PAN electrospinning was performed, thus establishing suitable compositional and processing parameters for obtaining homogenous fibers. Then, coaxial electrospinning of ABS and PAN solutions containing different amount of ZnO nanoparticles was carried out. The coaxial morphology of the nanofibers and ZnO distribution/dispersion were studied by the combination of several techniques such as scanning electron microscopy, X‐ray energy dispersive analysis, contact angle, and thermogravimetric analysis. The performance of the obtained membranes for chromium (VI) ions removal from aqueous solutions was assessed by photoreduction using ultraviolet–visible spectroscopy. Electrospun mats composed of ABS (core)/PAN (sheath) embedded with 30 wt % of ZnO nanoparticles exhibited the highest chromium photoreduction (about 80%), suggesting the potential use of these membranes as filters for water purification. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48429. Abstract : Core‐sheath composites fibers based on ABS/PAN‐ZnO nanoparticles.